Innovating Wellness: The Role of Fitness and Nutrition Entrepreneurship in Shaping Positive Body Image across Gender - Indira Priyadarshini; Dr. Tania Mishra (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Women are more affected by false beauty standards than men are, both mentally and physically. But a small but vociferous group is calling for changes in the health and wellness business. Do you know who owns businesses that encourage healthy living? The company is doing a lot to get away from damaging stereotypes and promote a more open and honest view of body acceptance, but these problems are still there. Many business entrepreneurs have become financially independent by realizing how important their bodies are and valuing them. Starting businesses that focus on health and questioning traditional gender roles are two ways that this dynamic is helping to make gender equality a reality. This study seeks entrepreneurial concepts that promote diversity, challenge established norms, and emphasize alternative perspectives through a narrative review and critical synthesis of health-related literature. To understand modern body positivity, one must look at it through a gendered lens. This essay does just that by looking at wellness businesses. The significance of entrepreneurs in shifting conventional narratives toward gender-inclusive, holistic health is highlighted in this sociology and health study, which establishes a connection between market innovation and shifting societal views of wellness and body image.